Adenylate Cyclase Toxin Tinkering With Monocyte-Macrophage Differentiation - Jawid Nazir Ahmad; Peter Sebo (Frontiers in Immunology, 2020)
Circulating inflammatory monocytes are attracted to infected mucosa and differentiate into macrophage or dendritic cells endowed with enhanced bactericidal and antigen presenting capacities. In this brief Perspective we discuss the newly emerging insight into how the cAMP signaling capacity of Bordetella pertussis adenylate cyclase toxin manipulates the differentiation of monocytes and trigger dedifferentiation of the alveolar macrophages to facilitate bacterial colonization of human airways.